Interleukin-17A regulates ependymal cell proliferation and functional recovery after spinal cord injury in mice - Hisao Miyajima; Takahide Itokazu; Shogo Tanabe; Toshihide Yamashita (Cell Death and Disease, 2021)
Abstract Ependymal cells have been suggested to act as neural stem cells and exert beneficial effects after spinal cord injury (SCI). However, the molecular mechanism underlying ependymal cell regulation after SCI remains unknown. To examine the possible effect of IL-17A on ependymal cell proliferation after SCI, we locally administrated IL-17A neutralizing antibody to the injured spinal cord of a contusion SCI mouse model, and revealed that IL-17A neutralization promoted ependymal cell proliferation, which was paralleled by functional recovery and axonal reorganization of both the corticospinal tract and the raphespinal tract. Further, to test whether ependymal cell-specific manipulation of IL-17A signaling is enough to affect the outcomes of SCI, we generated ependymal cell-specific conditional IL-17RA-knockout mice and analyzed their anatomical and functional response to SCI. As a result, conditional knockout of IL-17RA in ependymal cells enhanced both axonal growth and functional recovery, accompanied by an increase in mRNA expression of neurotrophic factors. Thus, Ependymal cells may enhance the regenerative process partially by secreting neurotrophic factors, and IL-17A stimulation negatively regulates this beneficial effect. Molecular manipulation of ependymal cells might be a viable strategy for improving functional recovery.